The Strategic Use of - Denham, Lee-Anne (My University, 2011)
Most companies today operate in a highly complex environment in which they need to find ways to remain competitive and generate shareholder value. Business Intelligence (BI) provides the mechanism to analyse vast volumes of data in order to generate insight into the operations of the business. This insight aids decisionmaking regarding changes to the environment within which companies operate. Companies can further increase the benefits derived from BI by employing it strategically. Therefore, the research questions were to determine the extent to which companies in South Africa were employing BI strategically and what factor aided or inhibited the strategic use of BI. Semi-structured interviews were used to gather the results for the research questions and content analysis was used to identify the key themes in the interview content. The research found that, although the reasons for companies using BI suggested the strategic use of BI, the prevalence of BI users was limited in organisations and the functionality provided by the solutions focused on operational issues. Key factors were identified that aided and inhibited the strategic use of BI. Companies therefore need to fully understand the value of strategic BI and assess whether these factors are inhibiting the benefits they derive from BI.
MBA - WBS
Keywords: Business intelligence systems; Business intelligence